Correlation of Handedness with Hand Length in Right Hander and Left Hander Medical Students in Bangladesh - Rahman, Md Shamsur; Sultana, Afrin; Momena, Zeenatul (Community Based Medical Journal, 2025)
A cross-sectional, analytical type study was performed in the Department of Anatomy, Dhaka Medical College, Bangladesh, from July 2016 to June 2017, to analyze the differences between right and left hand length and its correlation with handedness score in right hander and left hander medical students of Bangladesh. A total of 178 (52 right hander male, 52 left hander female, 40 left hander male and 34 left hander female) medical students participated in this study. Sample collection was done by convenient purposive sampling technique. History of any injury of upper limb was excluded to construct standard measurement. Handedness of each medical student was determined by the Edinburgh handedness inventory. Hand length was measured with the help of vernier calipers. Significant difference was observed between right and left hand lengths of the right hander (181.58±9.51 mm vs. 183.67±9.21 mm; P<0.001) as well as left hander male medical students (182.78±8.10 mm vs. 181.45±8.96 mm; P<0.05). Similarly, significant difference was observed between right and left hand lengths of the right hander (165.71±8.37 mm vs. 167.77±8.14 mm; P<0.001) as well as left hander female medical students (168.82±6.66 mm vs. 167.35±6.54 mm; P<0.001). However, handedness score showed non-significant negative correlation with right hand length (r=–0.178, P>0.05) and left hand length (r=–0.192, P>0.05) in right hander male. Similarly, in right hander female, non-significant negative correlation was found with right hand length (r=–0.034, P>0.05) and left hand length (r=–0.025, P>0.05). In left hander male, non-significant positive correlation was found with right hand length (r=+0.067, P>0.05) and left hand length (r=+0.107, P>0.05). In left hander female, non-significant positive correlation was found with right hand length (r=+0.234, P>0.05) and left hand length (r=+0.169, P>0.05). CBMJ 2025 July: vol. 14 no. 02 P:168-172